(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2014)
E-Commerce industry is booming in India, and m-Commerce is following its lead. With both big and small online businesses developing special mobile websites and apps, it is evident that even they have realised how prominent this platform is. In a country where there are over 930 Million mobile subscribers against 160 Million Internet users (Including 86 Million mobile Internet users) it is quite possible for m Commerce to become even bigger than e-Commerce. According to a report by Avendus, there were over 39 Million Smartphone users in India, but over 436 Million Internet capable mobile devices in use in India as of December 2013, thus forming a strong consumer base for m Commerce. And in India, there is a large young consumer base, who want fast instantaneous processes on the move. Even though e Commerce has spread its roots throughout the country, it still hasn’t reached the places where people have no broadband or no computer. M Commerce could and will change this. A mobile payment could be made by an app, data connection, IVR and even SMS, so anyone who has a bank account can make a transaction. Low rates of internet services will encourage people to use more of Mobile Internet, and eventually engage into m-Commerce as well. This paper is an attempt to study the cultural issues associated with the growth of m-commerce.